Implementation of Food Security Policies and Their Implications For Food Availability For Citizens - Lukum, Roni; Yunus, Resmiyati (Publikasi Indonesia, 2023)
Implementation of food security policies and their implications for food availability for community members (Study in the transmigration placement area of Wonosari District, Boalemo Regency, Gorontalo Province). The purpose of the study was to find out the implementation of the local government's food security policy in Wonosari District and its implications for food availability for residents in the Boalemo Regency of Gorontalo Province. And the benefits of research to determine the impact of implementing food security policies on the food availability of community residents in the Boalemo Regency area of Gorontalo Province. The method used in this research is with a qualitative type of research through a descriptive analysis approach. Based on the results of research, it shows that the food policy of the local government of Boalemo regency, Gorontalo Province, especially in the Wonosari sub-district area as a placement of transmigration residents, has had an impact on food availability for the local government of Boalemo Regency. This is shown by rice production, livestock production, vegetables (horticulture) and the very high trade business sector originating from Wonosari district. In addition, the assessment of the national resilience index in the Wonosari sub-district has been fulfilled as a manifestation of the implementation of food security policies. As evidence, the local government of Boalemo Regency has made efforts to improve the quality of life of its residents through education, health and community welfare policies in the form of ease of obtaining superior seeds, making irrigation, improving facilities and infrastructure to support food security, accelerating electricity in villages, opening access to clean water for its residents. Theresearch above has opened up the understanding of local ethnic residents about the importance of the presence of transmigration residents in the Boalemo district area for food availability. So that the results of the research have answered the hypothesis that the placement of transmigration residents in Wonosari sub-district will have the potential for friction that leads to conflicts between local ethnicities and transmigration residents.